Divine Justice in the Perspectives of the Muʿtazilah, Ashʿariyyah, and Maturidiyyah - Alqadri, Saripa Balqis; M, Mahmuddin; Abbas, Nurlaelah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The concept of divine justice is a central theme in Islamic theological discourse and is closely related to issues of divine will, human freedom, and moral responsibility. Differences in human conditions such as social inequality, suffering, and disasters have generated ongoing theological debates regarding the meaning and manifestation of God’s justice. This study aims to analyze and compare the concept of divine justice as articulated by three major Islamic theological schools, namely Muʿtazilah, Ashʿariyah, and Maturidiyah. This research employs a qualitative approach based on library research. The data are derived from primary sources consisting of classical Islamic theological works and secondary sources including scholarly books and academic journal articles relevant to the topic. Data analysis is conducted using a descriptive comparative method to examine similarities and differences among the theological perspectives based on their epistemological and doctrinal foundations. The findings reveal that Muʿtazilah understands divine justice through a rational framework that affirms full human freedom and asserts that God is obligated to act justly according to rational standards. In contrast, Ashʿariyah conceives divine justice as entirely grounded in God’s absolute will and power, which cannot be evaluated by human reason. Meanwhile, Maturidiyah adopts a moderate position by recognizing the capacity of reason to discern moral values while ultimately subordinating it to the authority of revelation. This study demonstrates that differing conceptions of divine justice reflect the diversity of Islamic theological approaches in addressing the relationship between divine sovereignty and human moral responsibility.